Clinicopathological Features of Young Versus Older Patients With Breast Cancer at a Single Pakistani Institution and a Comparison With a National US Database - Sana Zeeshan; Basim Ali; Khabir Ahmad; Anees B. Chagpar; Abida K. Sattar (Journal of Global Oncology, 2019)
PURPOSE: The age at which women present with breast cancer varies widely among nations, and breast cancer may behave differently in younger women. Differences in clinicopathological characteristics based on age have not been well characterized in Pakistani patients with breast cancer. METHODS: We conducted a retrospective review of patients with symptoms of breast cancer presenting to Aga Khan University Hospital (AKUH), a large tertiary care center in Pakistan, between 2001 and 2010; we compared young (≤ 40 years) versus older (> 40 years) patients in terms of their clinicopathological characteristics. We also compared this Pakistani cohort with the US population using data from the National Cancer Database (NCDB). RESULTS: A total of 1,334 patients with breast cancer presented to our center over the 10-year review period. The median age at diagnosis was 50 years, compared with 60 years for patients in the NCDB. In the AKUH cohort, younger patients were significantly more likely than their older counterparts to present with metastatic disease (13.1% v 10.8%; P < .01). They also were more likely to present with higher-grade tumors (grade 3: 40.1% v 28.3%; P < .001), have triple hormone receptor–negative phenotype (25.4% v 14.1%, P < .001), and have positive axillary lymph node involvement (70.9% v 57.5%; P < .001) compared with older women. Younger and older patients in the AKUH cohort tended to present with higher-stage disease (P < .001) and were more likely to have triple hormone receptor–negative disease (P < .001), compared with all patients in the NCDB and with those of Indo-Pakistani origin. CONCLUSION: Young Pakistani women, similar to their Western counterparts, present with more advanced disease and more aggressive tumor biology than their older counterparts.